'Who should do the caring'? Involved fatherhood and ambivalent gendered moral rationalities among cohabiting/married irish parents. Issue 1 (1st January 2016) - Ralph, David
Abstract : Drawing on qualitative couple interviews with cohabiting/married mothers and fathers, this paper examines accounts of involved fatherhood in contemporary Ireland. It shows that while the ideal of fathers as heavily involved in day-to-day parenting is widespread, the reality is somewhat different – and this despite increased participation of Irish mothers in the labour market. Given this mismatch between fatherhood ideals and realities, it begs the question: how do we account for this inequitable division of family work? Gender-differentiated parenting experiences, I argue, are strongly influenced by ambivalent attitudes on the part of both fathers and mothers. I argue that mothers draw on 'primarily mother' moral rationalities that associates 'good' mothering with large amounts of time in direct provision of childcare, while fathers display a 'primarily worker' rationality associated with strong commitment to the labour market. It is the clash of these contrasting normative societal demands that gives rise to a pervasive sense of ambivalence about 'who should do the caring'. This ambivalence, I demonstrate, is especially prominent in single-income families where the father is the sole breadwinner. In dual-income families, several parents go some distance towards reconciling these contradictory claims, these competing moral discourses.